The bZIP transcription factor HY5 interacts with the promoter of the monoterpene synthase gene QH6 in modulating its rhythmic expression - Zhou, Fei; Sun, Tian-Hu; Zhao, Lei; Pan, Xi-Wu; Lu, Shan (Frontiers in Plant Science, 2015)
The Artemisia annua L. β-pinene synthase QH6 was previously determined to be circadian-regulated at the transcriptional level, showing a rhythmic fluctuation of steady-state transcript abundances. Here we isolated both the genomic sequence and upstream promoter region of QH6. Different regulatory elements, such as G-box (TGACACGTGGCA, -421 bp from the translation initiation site) which might have effects on rhythmic gene expression, were found. Using the yeast one-hybrid and electrophoretic mobility shift assay (EMSA), we confirmed that the bZIP transcription factor HY5 binds to this motif of QH6. Studies with promoter truncations before and after this motif suggested that this G-box was important for the diurnal fluctuation of the transgenic β-glucuronidase gene (GUS) transcript abundance in Arabidopsis thaliana. GUS gene driven by the promoter region immediately after G-box showed an arrhythmic expression in both light/dark (LD) and constant dark (DD) conditions, whereas the control with G-box retained its fluctuation in both LD and DD. We further transformed A. thaliana with the luciferase gene (LUC) driven by an 1400 bp fragment upstream QH6 with its G-box intact or mutated, respectively. The luciferase activity assay showed that a peak in the early morning disappeared in the mutant. Gene expression analysis also demonstrated that the rhythmic expression of LUC was abolished in the hy5-1 mutant.